If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.5(x + -1) = 0.33(x + 1) Reorder the terms: 0.5(-1 + x) = 0.33(x + 1) (-1 * 0.5 + x * 0.5) = 0.33(x + 1) (-0.5 + 0.5x) = 0.33(x + 1) Reorder the terms: -0.5 + 0.5x = 0.33(1 + x) -0.5 + 0.5x = (1 * 0.33 + x * 0.33) -0.5 + 0.5x = (0.33 + 0.33x) Solving -0.5 + 0.5x = 0.33 + 0.33x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.33x' to each side of the equation. -0.5 + 0.5x + -0.33x = 0.33 + 0.33x + -0.33x Combine like terms: 0.5x + -0.33x = 0.17x -0.5 + 0.17x = 0.33 + 0.33x + -0.33x Combine like terms: 0.33x + -0.33x = 0.00 -0.5 + 0.17x = 0.33 + 0.00 -0.5 + 0.17x = 0.33 Add '0.5' to each side of the equation. -0.5 + 0.5 + 0.17x = 0.33 + 0.5 Combine like terms: -0.5 + 0.5 = 0.0 0.0 + 0.17x = 0.33 + 0.5 0.17x = 0.33 + 0.5 Combine like terms: 0.33 + 0.5 = 0.83 0.17x = 0.83 Divide each side by '0.17'. x = 4.882352941 Simplifying x = 4.882352941
| x=0.5(10x-40) | | 72842.976=2*3.14*1281.64+2*3.14*35.8*h | | 8u-4u=19 | | D=150-10P | | (x-2)35= | | 5x^2-14x-96=0 | | 6sinx+1=0 | | 4x-15=5+2r | | 15-5w+2w=-2(-3w+2)+19 | | 630.0096=2*3.14*19.36+2*3.14*4.4*h | | (x)+(2x)=90 | | -80(-40+39)= | | -3(-13)= | | -v+125=267 | | -v+125=266 | | -V+216=140 | | 7[3+4(7-2)]= | | 36-X=3X | | 25=a+8 | | 13-5n=-6(-n-8)+2(5n+2) | | 6a+5=14 | | 10b^2-31b-36= | | -25.294-0.8x=-3.2+2.7(2.7x+5.6) | | 2[3-(p+6)]-18=4(3+p) | | x^3-4x-5760=0 | | 4m-2=4m-14 | | 0.5(6x+10)+8=10 | | 20x-5x+2x=190 | | 1.88=4.9t^2 | | 8x-(-5x)+3=x-7+10 | | (8x+24)-4x=(4x+96)-4x | | 0.25x+0.15=2.00 |